Infographic Learning Media Based on The Values of Gayo Filigree Embroidery to Improve Student Character during The Covid-19 Pandemic - Sufandi Iswanto; Zulfan Zulfan; Saipullah Saipullah (Proceedings of AICS - Social Sciences, 2021)
This paper examines the development of infographic learning media based on Gayo filigree embroidery values to improve student character during the covid-19 pandemic. This study aims to explore, develop, and test the effectiveness of the media. The method used in this research is using the Borg Gall model. The results of the study indicate that so far teachers have used learning media and instilled character education. However, the material developed is only limited to the material contained in the textbooks. The development of historical infographic learning media based on Gayo filigree embroidery values is used as a solution for exploratory or preliminary studies. From the results of the media effectiveness test, it shows that the developed media can improve students' character.Keywords: Learning Media, Infographics, Gayo filigree embroidery Values, Character.